The impact of self-esteem and self-efficacy on the performance of medical personnel: The mediating role of job satisfaction - Sulaimiah; Nuruly, Santy; Suprayetno, Djoko; Wardani, Laila; Endri, Endri (Edelweiss Applied Science and Technology, 2024)
The study aims to investigate the impact of self-esteem and self-efficacy on the performance of medical personnel by making job satisfaction variables as mediators. The research design used is causal associative research. Data were collected from 87 respondents consisting of doctors, nurses, and midwives at private hospitals in Mataram City, namely Risa Hospital, Harapan Keluarga Hospital, and Siti Hajar Islamic Hospital. This study was analyzed using path analysis equipped with instrument tests using structural equation modeling (SEM). The research results revealed that self-esteem and self-efficacy have a positive and significant effect on the job satisfaction of medical personnel. Self-esteem and self-efficacy also have a positive and significant impact on performance. Job satisfaction has a positive and significant effect on the performance of medical personnel. Job satisfaction does not mediate the impact of self-esteem on performance. Self-efficacy also does not affect the performance of medical personnel through the mediation of job satisfaction. The study results provide practical implications for hospital management, such as improving the performance of medical personnel, and they must design and implement programs that can increase self-esteem, self-efficacy, and job satisfaction.